Analisis Perilaku Konsumen Rumah Tangga dalam Pembelian Ayam Potong di Distrik Merauke - Elsy Balawai; David Oscar Simatupang; Untari Untari (Musamus Journal of Livestock Science, 2020)
This research aims to analyze the factors consumer behaviour towards the purchase of chicken meat cut into traditional and modern markets on the market on the level of consumer households are there in the District of Merauke. This research was carried out in the District of Merauke for three (3) months, i.e. from April 2015 until June 2015. The basic method used in this research is descriptive method. Site selection research was done deliberately i.e. in the District of Merauke. Location of study housed in 8 subdistricts in Merauke District. The number of samples in this research is the 44 respondents. The type of the data being used is the primary data and secondary data obtained through the techniques of observation, and interviews. The analysis used was chi square analysis. The results showed that of the 44 respondents that influence consumer behavior in purchasing chicken pieces on traditional markets and modern market on the level of consumer households which is that decisions in the purchase of chicken pieces (Y) based on the type of work (X1) 0.035 is, income level (X1) is of the number of dependents, 0.128 family (X3) is based on the type, and 0757 jobs (X1) is of 0.001. And from the results of data processing carned showing that the decision in buying of chicken influential positive and significant is variable income (X2) was in 0,128 and variable namber of dependents (X3) was in 0,757.